HUBUNGAN ANTARA PENETAPAN TUJUAN, SELF-EFFICACY DAN KINERJA - Tutuk Ari Arsanti (Jurnal Bisnis dan Ekonomi, 2009)
and performance. Many students were participated in manipulation check andlaboratory experiment. Anagram was used in this experiment as individual assignmentand goal setting’s treatment. Self-efficacy were measured with 17 items, adapted andmodified from the Shere, at al. (1982). Scale assessing the strength of person’s efficacy.Performance was measured with score that was achieved by participant in the game.Path analysis was used in order to analyze the relationship between variables. ANOVAwas used to test the causal relationship between goal setting and performance. Linierregression was used to test the relationship between self-effiacy and performance.This research finding shows that causal relationship between goal setting andperfomance was not significant and the relationship between self-efficacy andperformance was significant.Key words: goal Setting – self-efficacy – performance